Functional Outcomes of Open Reduction and Internal Fixation in Proximal Humerus Fractures by Philos Plate - Shrestha, Shreshal; Kandel, Prakriti Raj; Shrestha, Bipan; Shrestha, Kishorman; Pandey, Subash; Chhetri, Dipendra Singh; Gharti, Sanjeeb Babu (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Proximal humerus fractures are one very common and usually occur in elderly people. These fractures are usually associated with some degree of comminution and deformity. Therefore, good anatomical reduction of fracture fragments and early mobilization are the main component for optimal outcomes of involved limb. This study was intended to evaluate the functional outcome of proximal humerus fracture in adults managed by open reduction and internal ﬁxation (ORIF) by proximal humerus interlocking osteosynthesis (PHILOS) plate. MATERIAL AND METHODS This prospective and observational hospital based study was carried out in Orthopedics Department of Universal College of medical Sciences-Teaching Hospital (UCMS-TH) from October 2021 to September 2023. All patients with proximal humerus fractures who fulﬁlled the inclusion criteria and who underwent open reduction and internal ﬁxation by PHILOS plate were enrolled in the study. Functional outcome was assessed according to Constant murley scoring system and Visual analogue score. Post-operatively patients were regularly followed at 6 weeks, 3 months and 6 months. RESULTS In this study of 60 cases, the mean age group was 55.38±11.40 years and male patients outnumbered female patients (39 males and 21 females). 36 cases (60%) were of right side and 24 (40%) were of left side. Majority of the fractures were due to fall injury (57%) followed by road trafﬁc accident (35%). The mean Constant Murley Score was 78.15±5.620 and VAS (visual analogue score) was 1.88±0.865. CONCLUSION Open reduction and internal ﬁxation by PHILOS plate is an effective procedure providing good anatomical restoration and early mobilization in proximal humerus fracture thus providing good functional outcome.